Nonlinear temporal dynamics of the cerebral blood flow response. - Miller, K; Luh, WM; Liu, T; Martinez, A; Obata, T; Wong, E; Frank, L; Buxton, R (2001)
The linearity of the cerebral perfusion response relative to stimulus duration is an important consideration in the characterization of the relationship between regional cerebral blood flow (CBF), cerebral metabolism, and the blood oxygenation level dependent (BOLD) signal. It is also a critical component in the design and analysis of functional neuroimaging studies. To study the linearity of the CBF response to different duration stimuli, the perfusion response in primary motor and visual cortices was measured during stimulation using an arterial spin labeling technique with magnetic resonance imaging (MRI) that allows simultaneous measurement of CBF and BOLD changes. In each study, the perfusion response was measured for stimuli lasting 2, 6, and 18 sec. The CBF response was found in general to be nonlinearly related to stimulus duration, although the strength of nonlinearity varied between the motor and visual cortices. In contrast, the BOLD response was found to be strongly nonlinear in both regions studied, in agreement with previous findings. The observed nonlinearities are consistent with a model with a nonlinear step from stimulus to neural activity, a linear step from neural activity to CBF change, and a nonlinear step from CBF change to BOLD signal change.